Analisis Eksegetis al-Ankabut: Reorientasi Nilai Teologis-Edukatif dalam Perspektif Lintas Zaman. - ria puspitasari; Iskandar (AR ROSYAD: Jurnal Keislaman dan Sosial Humaniora, 2026)
This research analyzes the parable of the spider in Surah al-Ankabut verse 41, aiming to uncover its profound meanings, review the perspectives of exegetes across generations, and identify the theological-educational values embedded within it. Employing a library research method and a thematic interpretive approach (tafsir maudū’i), this study comprehensively collects and analyzes all relevant verses related to the spider theme. The findings indicate that the spider's parable, despite positive characteristics like independence and persistence, fundamentally highlights the extreme fragility of its web as a shelter. Interpretations from the Mutaqaddimin period (Ibn Abbas and Ibn Jarir al-Tabari) focused on the weakness of idols as objects of worship. Mutaakhkhirin exegetes (Ibn Kathir and Al-Razi) expanded the meaning of this parable to include the weakness of any reliance on other than Allah, even encompassing syirik khafiy (minor polytheism). Meanwhile, contemporary exegetes (Sayyid Qutb and Wahbah al-Zuhayli) contextualized this parable to human reliance on worldly powers such as government, wealth, and knowledge. Overall, this parable emphasizes the value of monotheism, Allah's authority and omnipotence, and the helplessness and fragility of created beings in the face of divine power. It serves as an eternal guide for humanity to rely solely on Allah.